2016
DOI: 10.1093/femspd/ftw073
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella pertussismodulates human macrophage defense gene expression

Abstract: Bordetella pertussis, the etiological agent of whooping cough, still causes outbreaks. We recently found evidence that B. pertussis can survive and even replicate inside human macrophages, indicating that this host cell might serve as a niche for persistence. In this work, we examined the interaction of B. pertussis with a human monocyte cell line (THP-1) that differentiates into macrophages in culture in order to investigate the host cell response to the infection and the mechanisms that promote that intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…For example, suppressors of cytokine signalling (SOCSs) proteins SOCS3 and SOCS2 belonging to important family of inflammatory response regulators [58] were shown to augment the infection with M. tuberculosis and S. enterica [59,60]. Highly induced expression of SOCS3 in infected macrophages is also in line with previous experiments, showing increased expression of SOCS3 gene in B. pertussisinfected THP-1 macrophages [21]. Similarly, increased expression of IDO1, LAMP3 and MARCKS genes in infected cells may correlate with attenuation of innate immune response and increased intracellular survival as it was shown for Mycobacterium leprae infection of monocytes [61], S. typhimurium infection of HeLa cells [62] and Burkholderia thailandensis infection of THP-1 macrophages and epithelial A549 cells [63], respectively.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…For example, suppressors of cytokine signalling (SOCSs) proteins SOCS3 and SOCS2 belonging to important family of inflammatory response regulators [58] were shown to augment the infection with M. tuberculosis and S. enterica [59,60]. Highly induced expression of SOCS3 in infected macrophages is also in line with previous experiments, showing increased expression of SOCS3 gene in B. pertussisinfected THP-1 macrophages [21]. Similarly, increased expression of IDO1, LAMP3 and MARCKS genes in infected cells may correlate with attenuation of innate immune response and increased intracellular survival as it was shown for Mycobacterium leprae infection of monocytes [61], S. typhimurium infection of HeLa cells [62] and Burkholderia thailandensis infection of THP-1 macrophages and epithelial A549 cells [63], respectively.…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, mouse is not a natural host of B. pertussis and in our study we were interested in specific interaction with human macrophages rather than with complex mouse immune system. To avoid donor-to-donor variation observed in experiments with primary macrophages, we used the THP-1 monocyte-derived cells, a popular cell model for immune modulations studies [37] which has also been shown to be a good surrogate for primary cells in experiments with B. pertussis [21]. Profiling of human respiratory epithelial cells [38] and THP-1 macrophages [21] following B. pertussis infection was studied using DNA microarrays and quantitative PCR, respectively, however, global RNA-seq analysis of transcriptional responses of human phagocytic cells to B. pertussis cells has not been performed as yet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations